Effect of Frequency of Ejaculation on Semen Characteristics in Two Breeds of Turkeys (Meleagris gallopavo) Raised in a Tropical Environment - Zahraddeen, D.; Butswat, I.S.R.; Kalla, D.J.U.; Sir, S.M.; Bukar, M.T. (International Journal of Poultry Science, 2005)
A study was carried out at the Abubakar Tafawa Balewa University Farm, Bauchi (February - May, 2002) to investigate the effect of frequency of ejaculation (once, twice and thrice per week) on semen traits in exotic and local turkeys. The results showed that ejaculate volume, live spermatozoa, abnormal spermatozoa, sperm concentration and total sperm per ejaculate were significantly (P